Retr,ocecal hernia (Rieux Hernia): intestinal occlusion. - Farcic, Antonio; Schneeberger, Federico; Alves, Alberto; Montero, Mario; Cardeza, Héctor (Cirugía del Uruguay, 1976)
The authors report a case of occlusion of the small intestine in the retrocecal fossa which wa.s successfully treated. They. make sorne historie considerations about the denomination of Rieux hernia for this variety. They also discuss the anatomical, clinica1 and tberapeutical elements of this entity on the base of a bibliographic review in which they did not lind antecedents in the national literature.